2007
DOI: 10.1128/mcb.01506-06
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ALR (MLL2) Reveals ALR Target Genes and Leads to Alterations in Cell Adhesion and Growth

Abstract: ALR (MLL2) is a member of the human MLL family, which belongs to a larger SET1 family of histone methyltransferases. We found that ALR is present within a stable multiprotein complex containing a cohort of proteins shared with other SET1 family complexes and several unique components, such as PTIP and the jumonji family member UTX. Like other complexes formed by SET1 family members, the ALR complex exhibited strong H3K4 methyltransferase activity, conferred by the ALR SET domain. By generating ALR knockdown ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
350
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(380 citation statements)
references
References 50 publications
25
350
3
2
Order By: Relevance
“…These observations are also consistent with recent studies showing that deletion of MLL3 in NIH3T3-L1 cells results in a significant loss of H3K4me3 at the promoter region of the adipogenic marker gene aP2 . Moreover, B-cell-specific knockout of PTIP, a subunit associating with MLL3/MLL4 complexes (Cho et al 2007;Issaeva et al 2007), results in a loss of H3K4me3 at specific Igh switch regions upon LPS stimulation (Daniel et al 2010). These seemingly contrasting results potentially point to a model in which RbBP5 phosphorylation can act as a switch increasing MLL3 kinetics, facilitating the formation of H3K4me1 that can potentially be further methylated to ultimately form H3K4me2/3.…”
mentioning
confidence: 84%
“…These observations are also consistent with recent studies showing that deletion of MLL3 in NIH3T3-L1 cells results in a significant loss of H3K4me3 at the promoter region of the adipogenic marker gene aP2 . Moreover, B-cell-specific knockout of PTIP, a subunit associating with MLL3/MLL4 complexes (Cho et al 2007;Issaeva et al 2007), results in a loss of H3K4me3 at specific Igh switch regions upon LPS stimulation (Daniel et al 2010). These seemingly contrasting results potentially point to a model in which RbBP5 phosphorylation can act as a switch increasing MLL3 kinetics, facilitating the formation of H3K4me1 that can potentially be further methylated to ultimately form H3K4me2/3.…”
mentioning
confidence: 84%
“…These results show that the coordinated regulation of histone modifications by a repressive complex, containing KMT and KDM activities, may be important for the transcriptional regulation of different genes during differentiation and development. Interestingly, similar biochemical structures containing KMT and KDM activities have also been reported for the TrxG-like MLL complex, where the MLL2 and ASH2 H3K4me3 KMTs are associated in a complex containing the H3K27me3-specific demethylase UTX Issaeva et al 2007;Lee et al 2007b). These findings indicate that these different enzymatic activities function together to coordinately regulate lysine methylation and transcription.…”
Section: Histone Methylation and Demethylationmentioning
confidence: 81%
“…Issaeva et al 8 determined the MLL2 protein to have a significant role in promoter and transcription initiation sites of target genes via the role as a histone modifier. Issaeva found that in MLL2-knockout mice models, there were 20 genes most significantly downregulated, which comprised various functions, including cell migration, growth adhesion and transcriptional regulation.…”
Section: Mll2 and The Ks Phenotypementioning
confidence: 99%
“…ENO3 is known to be responsible for glycolysis, muscle development and regeneration, TNNT2 for regulation of muscle contraction and development, whereas NPR3 involvement in skeletal development. 8 …”
Section: Mll2 and The Ks Phenotypementioning
confidence: 99%
See 1 more Smart Citation